Anthropological study for the determination of the Europid and Negroid characteristics on facial bones of human fetuses - Kósa, Ferenc (Acta Biologica Szegediensis, 2002)
During my 3-month long scholarship in the Smithsonian Institute in 1991, I carried out metric and comparative anatomical (anthropological) examinations on the collection of fetal/newborn skeletons of the Anthropological Institute of the National Museum of Natural History, Washington, D.C. I determined 85 sizes of 50 characteristic bones of about 350 complete fetal/new-born skeletons in standardized conditions. In the study of facial bones and during the mathematical-statistical analyses, the data of 37 Europid and 27 Negroid and 47 mixed (Mulatto) skeletons were taken into account. According to my analyses the facial bones of the two human races differ significantly in both forms and sizes. The most characteristic formal anthropological features can be identified on the frontal process of the maxilla, the surface of the palate of the maxilla, the plate forming the nasal septum (vomer), the os zygomaticum and the mandibe.The applied mathematical-statistical methods (multiple comparison (Bonferroni), variance analysis, regression and correlation analysis and multivariant discriminant analysis) confirmed the anthropological characteristics and the varied formal differences that are visible to the naked eye. In the forensic medical and the anthropological practice, the possibility of the discrimination of the characteristics of the two main races (and possibility of the determination of the Europid and the Negroid characteristics) can be used with reasonable professional accuracy.